Komintern w świetle polskiej publicystyki przeciwkomunistycznej II Rzeczypospolitej. Przyczynek do badań nad polskim antykomunizmem - Sacewicz, Karol (Komunizm: System - Ludzie - Dokumentacja, 2023)
Anti-Communism attitudes were commonplace in inter-war Poland, present both in the circles of the left-wing independence movement, people’s parties, Christian democratic parties, and in the conservative or national political groups. To a great extent, this widespread dislike for Communism and Communists was a result of social antiCommunist initiatives in Poland that had recognized the Communist threat, e.g. the Central Office of Anti-Communist Agreement. Thanks to their activities, especially those of journalistic nature, the citizens of the Second Polish Republic were able to see the true nature of the Communist party. The acquisition, analysis, and dissemination of information that revealed the real identity of the Communist International were some of the key elements in the process of recognizing the Communist movement. Showing the Comintern as a subordinate center of the Communist movement controlled by the rulers from the Kremlin made it possible to understand what the Comintern was and whose commands and orders it followed unconditionally, as well as to understand particular communist parties. This article presents the scope of information on the Comintern at the disposal of the Polish anti-Communist factors.